A school fluoride varnish program for Aboriginal children in rural New South Wales, Australia. (22nd June 2019) - Dimitropoulos, Yvonne; Gwynne, Kylie; Blinkhorn, Anthony; Holden, Alexander
Abstract: Issue addressed: Australian Aboriginal children are less likely to access preventive oral health services such as fluoride varnish. The regular application of fluoride varnish can prevent dental caries. This study aims to determine if a school‐based fluoride varnish program can provide Aboriginal children with at least three fluoride varnish applications over 12 months and whether the routine application of fluoride varnish for Aboriginal children in schools is a feasible approach for oral health promotion in Aboriginal communities. Methods: A school fluoride varnish program was co‐designed with Aboriginal communities in Central Northern New South Wales, Australia and implemented in three schools where majority of enrolled children are Aboriginal. Four "fluoride varnish days, " 3 months apart, were held at each school over the 12‐month study period. On each "fluoride varnish day" an oral health therapist applied fluoride varnish to all children included in the study. Results: This study took place between January and December 2017. About 153 children were eligible to participate and 131 (86%) were consented into the program by a parent or guardian. A total of 104 children were enrolled for the entire 12‐month study period and included in the analysis. Majority of children (65.4%) received at least three fluoride varnish applications, with an average of 70% of students receiving an application of fluoride varnish on each "fluoride varnish day." Conclusions: School‐based fluoride varnish programs, co‐designed with local Aboriginal communities, may be a feasible approach to oral health promotion aimed at improving the oral health of Aboriginal children. Summary: This study aimed to improve access to fluoride varnish for Aboriginal children in Central Northern NSW. Four "fluoride varnish days, " each three months apart, were held in three schools over 12 months. Majority of children (65.4%) received at least three fluoride varnish applications during the fluoride varnish program.